Comparison of growth performance and rumen metabolic pathways in sheep and goats under the same feeding pattern - Lin, Xueyan; Ju, Lin; Cheng, Qianjin; Jiang, Yue; Hou, Qiuling; Hu, Zhiyong; Wang, Yun; Wang, Zhonghua (Frontiers in Veterinary Science, 2023)
Diet and species are important factors affecting the rumen microbiota, with roughage stimulating rumen development and concentrate feeds being broken down by Ruminal flora decompose to provide the organism with a large amount of energy. The aim of this study was to explore the effects of host and dietary factors on rumen flora composition and diversity, as well as on host metabolism.This paper reports a study on five month-old male Small Tail Han Sheep and five month-old male Boer Goat, each with an average weight of 33.87 ± 1.70 kg. Five animals of each species were divided into S group (Small Tail Han Sheep) and B group(Boer Goat). The experiment was carried out in periods X and Y. The rations were fed with a 3:7 and 5:5 ratio of concentrate to roughage, respectively. Growth performance was measured by weight increase index. Results showed that under the same raising conditions, the ratio between body weight increases and the amount of feed was lower in S than in B group; but the differences were not significant. According to the analysis of the apparent digestibility ratio of nutrition ingredients, the XS group had a significantly higher apparent digestibility for acid detergent fiber than the XB group (P＜0.05). Analysis of rumen fermentation parameters showed that the rumen pH has no significant differences between XS and XB group,it was significantly lower in YS than in the YB group. The XS group contained a significantly lower content of total volatile fatty acids than XB group (P＜0.05). Analysis of the 16S rDNA sequencing results revealed that compared to the B group, the S group was highly enriched with the following bacteria: Proteobacteria, γ Gammaproteobacteria, Aeromonadales, and Succinivibrionaceae. Thus, it can be concluded that the host species affected the abundance and the diversity of rumen bacteria. Feed utilization efficiency of Small Tail Han Sheep was higher than Boer Goats, which might be specifically associated with Succinivibrionaceae. Results from this study show that animals belonging to the same family but different genus and species can differ in metabolic pathways even when they are provided with the same animal feed.